Identification of a second HOXA2 nonsense mutation in a family with autosomal dominant non‐syndromic microtia and distinctive ear morphology. Issue 5 (13th September 2016) - Piceci, F.; Morlino, S.; Castori, M.; Buffone, E.; De Luca, A.; Grammatico, P.; Guida, V.
Abstract : Microtia is a congenital defect affecting external ears, which appear smaller and sometimes malformed. Here we describe a five‐generation family with isolated bilateral microtia segregating as an autosomal dominant trait. Similar features have been previously observed in an autosomal dominant family with non‐syndromic microtia and hearing loss segregating with a HOXA2 nonsense variant. HOXA2 biallelic mutations were also described in an inbreed family with autosomal recessive microtia, hearing impairment and incomplete cleft palate. In our family, sequence analysis detected a heterozygous protein truncating nonsense variant [c.670G>T, p.(Glu224*)] segregating in all affected individuals and absent in public databases. This study confirms the role of HOXA2 gene in dominant isolated microtia and contribute to further define the dysmorphogenetic effect of this gene on ear development. Abstract : Schematic representation of the HOXA2 gene and corresponding protein product showing the position of the c.670G > T p.(Glu224*) mutation and recognized protein domains.